Analisis Sistem Pendidikan sebagai Sistem Terpadu dalam Meningkatkan Pembelajaran - Habsy, Bakhrudin All; Harianto, Ine Muro'afah; Danendra, Naufal Daffa (TSAQOFAH, 2025)
Education is an integral part of human life, where every individual receives education from their parents after birth. Educating a child from an early age is part of early education provided by the family, which gradually extends to education within certain institutions and the broader community. Education is crucial for human life, serving as a conscious effort to humanize individuals. In the educational process, it is not solely the responsibility of schools; all elements must play an equal role in advancing education. All components must contribute (Ika Purwaningsih, 2022) (Abd Rahman BP S. a., 2022) and connect with each other in developing educational institutions or sustaining the educational process. A system is a complex unit of interconnected components working together to achieve optimal goals. The components that enable the educational process include educational objectives, students, education providers, parents, teachers/educators, community and religious leaders, the educational interaction between students and educators, and the content of education.